PENGARUH PROFITABILITY, LEVERAGE, AUDIT QUALITY, DAN FAKTOR LAINNYA TERHADAP TAX AVOIDANCE - Fransisca Sherly; Yohanes (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to obtain empirical evidence on the effect of profitability, company size, leverage, capital intensity, institutional ownership, sales growth, audit quality, and audit committee on tax avoidance which become a proxy of Effective Tax Rate (ETR). The population of this research is 204 manufacturing companies that are listed in Indonesia Stock Exchange (IDX) from 2018 to 2020. Samples are obtained through purposive sampling method The sample taken for this research is 62 companies, consisting of 186 data. The analysis method used in this research is multiple regression. This research proves that profitability has an effect on tax avoidance. Meanwhile, company size, leverage, capital intensity, institutional ownership, sales growth, audit quality, audit committee has no effect on tax avoidance. Profitability has an effect on tax avoidance, the reason being that company's with large sum of profit will affect the amount of tax that's need to be paid, making companies to look for flaws to minimize the tax to earn maximum profit. This research is expected to give implication to companies to prioritize internal wellfare through gross up method, rather than raising the company's profit that will be followed by the increased of tax burden. This is caused by minimizing the amount of tax payable, that will decrease the company's tendencies in doing tax avoidance practices. This research has new addition and update such as adding sales growth, audit quality, and audit committee as variables and the period used for this research is 2018-2020